Hybrid Photodetectors: Transition‐Metal‐Carbide (Mo2C) Multiperiod Gratings for Realization of High‐Sensitivity and Broad‐Spectrum Photodetection (Adv. Funct. Mater. 48/2019). (26th November 2019) - Jeon, Jaeho; Choi, Haeju; Choi, Seunghyuk; Park, Jin‐Hong; Lee, Byoung Hun; Hwang, Euyheon; Lee, Sungjoo
Abstract : In article number 1905384, Euyheon Hwang, Sungjoo Lee, and co‐workers report a hybrid photodetector consisting of a 2D semiconductor (MoS2 ) integrated with multiple grating metallic stripes (Mo2 C), which demonstrates broad spectral detection of light with high sensitivity, overcoming the inherent weakness of conventional 2D photodetectors and opening up possibilities for next‐generation photoelectric device technology by providing new functionalities for high sensitivity and effective broad‐spectrum photodetection.